The impact of vaccination status on COVID-19 cases: a case study in Pahang / Nur Hazwani Aqilah Abdul Wahid and Nurmarni Athirah Abdul Wahid - Abdul Wahid, Nur Hazwani Aqilah; Abdul Wahid, Nurmarni Athirah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
COVID-19 refers to the infectious disease known as coronavirus disease, distinguished by its transmission within the environment and attributed to the viral variant SARS-CoV-2. The aforementioned illness has resulted in significant levels of morbidity and mortality. Despite the implementation of diverse regional and national non-pharmaceutical interventions, including travel restrictions, social distancing measures, stay-at-home orders, and lockdowns, numerous countries are still grappling with the escalated situation of COVID-19 cases. The vulnerability of the global population to COVID-19 is widespread, emphasising the imperative of developing and deploying a potent vaccine. Several countries have highlighted the significance of vaccinations and their association with the daily incidence and mortality rates of COVID-19. Therefore, this study aimed to identify the association between the documented count of individuals who have not received vaccinations and the daily incidence of COVID-19 cases in Pahang, Malaysia. Based on the Spearman rank correlation analysis, its revealed that the use of vaccinations plays a pivotal role in mitigating the likelihood of contracting COVID-19 within the region of Pahang. The increase in reported cases of individuals in the state of Pahang who have not been vaccinated correlates with an increase in the daily incidence of COVID-19 cases. The results obtained from this study offer valuable insights into the epidemiological patterns of COVID-19 in the Pahang region. Also, these emphasis the significance of COVID-19 vaccination in mitigating the incidence of outbreaks and fatalities.